THE Local Wisdom as a Form of Development Principles of Environmental Sustainability in Indonesia - Nurhasan Mustopa; Nurul Chotidjah (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Abstract. This research is important to obtain the concept of developing the Principles of Environmental Sustainability in Indonesia, in order to preserve the marine environment againts various forms ofviolations in the field of marine fisheries. The Principle of Environmental Sustainability is a moral approach and emphasizes more on preventive measures in the preservation of the environment in general and in particular the marine environment. For conditions in Indonesia, there is a potential for local wisdom of the community of an area spread throughout the archipelago as a form of real efforts to involve the community in the preservation of the marine enviroment. This research was carried out using a normative juridical approach, qualitative legal analysis with legal interpretation methods, and literartur studies. The inclusion of Local Wisdom in the preservation of the marine environment is an important instrument as a form of Development of Environmental Sustainability Principles. The existence and role of local wisdom of coastal communities that are evenly distributed throughout the archipelago conceptually have the opportunity to be included as a form of the developing the Principles of Environmental Sustainability in order to support the effectiveness and efficiency of monitoring the conservation of marine fishery resources.